Time-resolved Fourier transform emission spectroscopy of He/CH4 in a positive column discharge - Civiš, Svatopluk; Kubelík, Petr; Ferus, Martin (The journal of physical chemistry. A, 2012)
Time-resolved Fourier transform infrared emission spectroscopy was applied to the study of a pulsed discharge in a He/CH(4) mixture. The dynamics of the formation and decay of acetylene ν(3) (3289 cm(-1)), methane ν(3) (3019 cm(-1)) and ν(1) (2917 cm(-1)), the CH radical electronic ground state X(2)Π(r) (2309-2953 cm(-1)), C(2) Bernath electronic transition B(1)Δ(g)-A(1)Π(u) (3337-3606 cm(-1)), molecular hydrogen emission transitions 5g-4f and 2p-2s, atomic hydrogen, and atomic helium were monitored in the 1800-4000 cm(-1) region. The time profile of the rotational and vibrational temperature of the CH radical was obtained for a 30 μs time interval during and after the discharge pulse. A kinetic model was used for the study of the chemical dynamics of the formation and decay of the individual fragments. The results from the model were compared to the experimental emission spectra.